Update on novel blood-based biomarkers for lupus nephritis beyond diagnostic approaches - José L. Maravillas-Montero; Raúl F. Reyes-Huerta (Permanyer, 2022)
Systemic lupus erythematosus (SLE) is a chronic inflammatory autoimmune disease with a wide range of clinical presentations. Lupus nephritis (LN) is a frequent complication of SLE, representing a significant cause of morbidity and mortality in these patients. In addition, LN diagnosis remains suboptimal in most clinical contexts. The current gold standard for LN clinical diagnosis is a renal biopsy. Still, the invasiveness of this technique is an obstacle to the early detection of renal involvement and further monitoring of treatment results. Consequently, there are different areas for improvement in the field of LN, such as the search for novel non-invasive clinical biomarkers with an adequate correlation between clinical manifestations and actual histological damage. Although urine component-related studies are promising, the more robust blood/serum biomarkers may still be helpful in developing point-of-care systems that can be adapted to most clinical scenarios. Therefore, this brief review aims to highlight and summarize some of the most recently reported non-classical serum/blood potential LN biomarkers.